Genetic epidemiology of familial Mediterranean fever through integrative analysis of whole genome and exome sequences from Middle East and North Africa. Issue 1 (26th September 2017) - Koshy, R.; Sivadas, A.; Scaria, V.
Abstract : Familial Mediterranean fever (FMF), an autosomal recessive and rare autoinflammatory disease is caused by genetic mutations in the MEFV gene and is highly prevalent in the Mediterranean basin. Although the carrier frequency of specific disease variants in the MEFV gene has been reported from isolated studies, a comprehensive view of variants in the Mediterranean region has not been possible due to paucity of data. The recent availability of whole‐genome and whole‐exome datasets prompted us to study the genetic epidemiology of MEFV variants in the region. We assembled data from 5 datasets encompassing whole‐genome and whole‐exome datasets for 2115 individuals from multiple subpopulations in the region and also created a compendium for MEFV genetic variants, which were further systematically annotated as per the American College of Medical Genetics and Genomics (ACMG) guidelines. Our analysis points to significant differences in allele frequencies in the subpopulations, and the carrier frequency for MEFV genetic variants in the population to be about 8%. The MEFV gene appears to be under natural selection from our analysis. To the best of our knowledge, this is the most comprehensive study and analysis of population epidemiology of MEFV gene variants in the Middle East and North African populations. Abstract :